Cooperative teamwork for quality customer service in the Hong Kong shiprepair yards environment - Ng, Peter Yip-Chuen (Curtin University, 2003)
During the turbulent times facing contemporary organisations, managers and employees need a precise understanding of the nature of team dynamics that develops quality service to customers. Extensive literature searches reveal few research studies focused on the nature of teamwork, which develops value to customers. The purpose of this study is to examine the value of teamwork for providing quality service within the Hong Kong shiprepair industry, outline the insight gleaned and recommend future research. This study aims to link empirically the Western developed Deutsch's (1949a, 19496, 1973, 1980, 1985, 1990) Theory of Cooperation and Competition with the innovation of teamwork and to assist in understanding the variance in the performance of these teams. Literature suggests that the relationships and interaction within the work teams can very much impact the overall performance of these work teams. The extent that these work teams are able to develop cooperative goals can promote productive and constructive communication and problem solving (constructive controversy) in their interactions. A constructive interaction leads to team members' perception of high team confidence. With trust, strong work relationship, team morale and perceived confidence, team effectiveness is enhanced on quality customer service (Alper, Tjosvold and Law, 1998; Tjosvold, Hui and Law, 1998; Tjosvold, Moy and Sasaki, 1996, 1999; Wong et al., 1999). The research also tests the extent of impact of traditional Chinese values of power distance and collectivism as contributing to cooperative goals and encourages an openminded discussion of opposing views (constructive controversy). It proposes that by adopting cooperative goals, shiprepair yard management in Hong Kong may meet the twin challenges of involving employees fully into the organisation and providing quality service to customers.The result suggests that the Western derived Theory of Cooperation and Competition, if appropriately and skillfully expressed, might have the potential as one alternative to understand the goal interdependence dynamics as experienced by the Hong Kong Chinese in the shiprepair industry. Nevertheless, the result is not confirmatory to the main hypothesis of the study that team confidence is significantly related to quality customer service. Findings of this study question whether a Western theory or research instrument derived is appropriate for application to a Chinese work setting (Bond and Wang, 1983). Although it is useful to test concepts developed in one culture to another, yet theories from the West cannot be assumed to apply in the East (Hofstede, 1993; Triandis, 1983). An important finding of this research is, however, that this Western derived theory might not be suitable to be applied in a work group of very low levels of education and/or low exposure to the modern workplace practice and Western influences.